The oxytocin receptor antagonist, Atosiban, activates pro-inflammatory pathways in human amnion via Gαi signalling. (15th January 2016) - Kim, Sung Hye; MacIntyre, David A.; Hanyaloglu, Aylin C.; Blanks, Andrew M.; Thornton, Steven; Bennett, Phillip R.; Terzidou, Vasso
Abstract: Oxytocin (OT) plays an important role in the onset of human labour by stimulating uterine contractions and promoting prostaglandin/inflammatory cytokine synthesis in amnion via oxytocin receptor (OTR) coupling. The OTR-antagonist, Atosiban, is widely used as a tocolytic for the management of acute preterm labour. We found that in primary human amniocytes, Atosiban (10 μM) signals via PTX-sensitive Gαi to activate transcription factor NF-κB p65, ERK1/2, and p38 which subsequently drives upregulation of the prostaglandin synthesis enzymes, COX-2 and phospho-cPLA2 and excretion of prostaglandins (PGE2 ) (n = 6; p < 0.05, ANOVA). Moreover, Atosiban treatment increased expression and excretion of the inflammatory cytokines, IL-6 and CCL5. We also showed that OT-simulated activation of NF-κB, ERK1/2, and p38 and subsequent prostaglandin and inflammatory cytokine synthesis is via Gαi−2 and Gαi−3 but not Gαq, and is not inhibited by Atosiban. Activation or exacerbation of inflammation is not a desirable effect of tocolytics. Therefore therapeutic modulation of the OT/OTR system for clinical management of term/preterm labour should consider the effects of differential G-protein coupling of the OTR and the role of OT or selective OTR agonists/antagonists in activating proinflammatory pathways. Highlights: Atosiban activates inflammatory pathways via PTX-sensitive Gαi signalling. OT drives proinflammatory pathways via Gαi−2 and Gαi−3 but not Gαq . Atosiban fails to inhibit the OT-mediated proinflammatory effects and mimics the effects of OT on its own.